Pengaruh HPMC Gel Ekstrak Etanol Buah Belimbing Wuluh (Averrhoa Bilimbi L.) Terhadap Sifat Fisik dan Aktivitas Antibakter - Ferdy Firmansyah jurnal editor (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id)
Bilimbi fruit (Averrhoa bilimbi L) has a antibacterial activity. Ethanol extract of bilimbi fruit is a potentially clear up acne which is caused bybacterium Propionibacterium acnes. This research is conducted to determine the effect of HPMC of bilimbi fruit ethanol extract gel on physicalnature and the activity of P. acnes. Bilimbi fruit liquid extract is obtained using maceration method with ethanol 80%. It is evaporated, the liquidextract becomes condensed. This research use three variants each contains 5,0%; 7,0%; and 9,0% of basic of HPMC. The test of organoleptic,homogenity, pH, and gel physical nature that embody adhesion test, scatter test, viscosity test are conducted on the gel. Antibacterial activity test wasconducted using diffusion method (secara sumuran). The antibacterial activity was measured by the size of its diameter of inhibitory zone which wasform in the media. The result data of physical nature of gel is analyzed by linear correlation of regression. Meanwhile, the result data of antibacterialactivity test was analyzed by statistical test using the method of ANOVA. The result of this research shows that when the level of HPMC isincreasing, its adhesion and its viscosity is getting tighter. Analytical result statistically shows that the antibacterial activity of the gel has the sameinhibitory zone with extract and peroxide benzoyl.